METODE DISKUSI DILEMA MORAL DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK KELAS VII MTS AN-NUR MAKASSAR - Ina Maga, Rimatir; Mustamin; Raehana, Syarifa; Syahid, Akhmad; Hasriani, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the implementation of the Moral Dilemma Discussion method to improve students’ learning achievement in the Akidah Akhlak subject for seventh-grade students at MTs An-Nur Makassar. The objectives of this research include describing the learning process using the Moral Dilemma Discussion method and evaluating students’ learning achievement in the context of Akidah Akhlak learning.This research employed a classroom action research method consisting of two cycles. Each cycle included planning, action, observation, and reflection as the main components. The research subjects consisted of 28 seventh-grade students, including 23 male students and 5 female students.Data were collected through observation and documentation techniques. The results of the study indicate that the implementation of the Moral Dilemma Discussion method successfully improved students’ learning achievement in the Akidah Akhlak subject at MTs An-Nur Makassar. In Cycle I, the average score was 72.43, with 46% of students categorized as having Poor achievement. However, in Cycle II, a significant improvement occurred, with the average score increasing to 98.5, and all students achieving the Very Good category, exceeding the minimum mastery criteria (KKM).The findings of this study conclude that the Moral Dilemma Discussion method is effective in improving students’ learning achievement.